2022
DOI: 10.1111/bjh.18365
|View full text |Cite
|
Sign up to set email alerts
|

Timing of referral to outpatient palliative care for patients with haematologic malignancies

Abstract: Summary Outpatient palliative‐care facilitates timely supportive‐care access; however, there is a paucity of studies on the timing of referral in the outpatient setting for patients with haematologic malignancy. We examined the trend in timing of outpatient palliative‐care referrals over a 10‐year period in patients with haematologic malignancies at our comprehensive cancer centre. We included consecutive patients with a diagnosis of haematologic malignancy who were seen at our outpatient palliative‐care clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The literature contains evidence that a shared path between PC and aggressive curative treatment (such as conditioning chemotherapy and related transplantation) is possible at the same time, accepted by patients, and has positive outcomes [ 32 , 33 ]. An outpatient observational study of patients with acute myeloid leukaemia revealed that those who received early palliative supportive care had a greater quality of life and lower rates of treatment aggressiveness at the end of life [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains evidence that a shared path between PC and aggressive curative treatment (such as conditioning chemotherapy and related transplantation) is possible at the same time, accepted by patients, and has positive outcomes [ 32 , 33 ]. An outpatient observational study of patients with acute myeloid leukaemia revealed that those who received early palliative supportive care had a greater quality of life and lower rates of treatment aggressiveness at the end of life [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, longitudinal outpatient PC for people with hematologic malignancies is feasible and has benefits upstream from the end-of-life period. 17 Large, multisite, and controlled trials are needed to confirm our findings and determine which aspects of PC are most impactful.…”
mentioning
confidence: 63%
“…There is evidence in the literature that a shared path between PCs, simultaneously with aggressive treatments and related transplantation with curative intent, is feasible and accepted by patients and with positive results [32,33]. An observational outpatient study based on patients with acute myeloid leukemia shows that those who received early palliative supportive care demonstrated a better quality of life and low rates of treatment aggressiveness at the end of life [34].…”
Section: Discussionmentioning
confidence: 99%